Confucius Institutes - Soft Power or Trojan Horse? View from the Russian Far East - Natalia V. Khisamutdinova; Yue Yang (Vestnik RUDN. International Relations, 2024)
Using the example of the Far Eastern Federal District, the article examines the role of Confucius Institutes, educational institutions that China has established in various countries since 2004 to teach Chinese language and culture. The relevance of the research is linked to the growing criticism of the dual function of these organizations. On the one hand, these Institutes are considered as a soft power instrument capable of creating China’s positive image and increasing its global influence through cultural and educational contacts. On the other hand, there are cases of Confucius Institutes acquiring hard power functions, allowing China to implement its strategic goals in other areas unrelated to education and culture. This has prompted reproaches from partner countries. These moments are especially relevant in the Russian Far East, given its close proximity to China, the considerable length of the Russian-Chinese border, and the critical demographic situation in the Russian Far East. The goal of the research is to identify whether regional factors support the criticism leveled at the Confucius Institutes and, subsequently, to propose measures to mitigate China’s hard power influence in the region. By analyzing the Institutes’ activities in the Russian Far East, the authors reveal three main aspects confirming their hard power functioning. The Confucius Institutes promote China’s ‘peaceful’ expansion; they increase the internationalization of Chinese education and contribute to the development of national culture. The authors conclude that when analyzing the pros and cons of Confucius Institutes, it is important to take into account the economic and political situation in the region where they operate. Otherwise, they risk being accused of serving as a Trojan horse. The article is based on recent Russian and Chinese sources, including academic writings and mass media publications, as well as the authors’ empirical research.